2013
DOI: 10.4012/dmj.2012-227
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy observation of enamel surfaces treated with selfetching primer

Abstract: Orthodontists use a self-etching adhesive system when attaching brackets to enamel. The purpose of this study was to evaluate the erosion effects of common clinically used adhesive systems on human enamel surfaces by atomic force microscopy (AFM). Four commercially available adhesive systems (i.e., Kurasper F, Beauty Ortho Bond, Orthophia LC, and Transbond XT) were applied to ground enamel surfaces of extracted human teeth. Enamel surface roughness (ESR), absolute depth profile (ADP), and surface hardness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…However, phosphoric acid etching causes a greater degree of enamel loss 14) . Hashimoto et al 37) , evaluating the erosion of BO and TX on enamel by atomic force microscopy, observed that TX increased the porosity of the enamel surface and significantly increased the enamel loss. Scougall-Vilchis et al 18,23,26) reported that in scanning electron microscopy (SEM) images of the enamel surface morphology, BO induced more conservative effects than did the acid-etching system.…”
Section: Discussionmentioning
confidence: 99%
“…However, phosphoric acid etching causes a greater degree of enamel loss 14) . Hashimoto et al 37) , evaluating the erosion of BO and TX on enamel by atomic force microscopy, observed that TX increased the porosity of the enamel surface and significantly increased the enamel loss. Scougall-Vilchis et al 18,23,26) reported that in scanning electron microscopy (SEM) images of the enamel surface morphology, BO induced more conservative effects than did the acid-etching system.…”
Section: Discussionmentioning
confidence: 99%
“…The AFM observation method we used is a valuable method of assessing the effects of different substances or procedures used in the oral environment. This method allows us to determine the qualitative structural changes in the enamel and the dentine samples [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The erosion effects are different compared to the acidity of treating agents (acid, adhesives, etc.) and are related with clinical effects [58]. Surface hardness of enamel may be determined on AFM images based on the curve of cantilever force [59,60].…”
Section: Resultsmentioning
confidence: 99%